Produksi Katup Bola Rumah SS304 Ukuran 0,5 Inci dengan Kapasitas 2 Biji per Jam - Fanni Cicilia Krisani; Syamsul Hadi; Dhia Kemal Ramadhan Wiyono; Aulia Tri Saputra; Hilmi Andyan Rahmaputra (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
Structural leakage of ball valves in piping systems in industrial areas and in household environments is a problem encountered in the field. The production objective is to obtain a ball valve with a valve housing made of stainless steel, SS304 with a valve ball diameter of 0.5”. The production method includes: design of a 0.5” ball valve; 3D geometric modeling and simulation using CAD/CAM software to extract numerical codes (G-code) and determine the cutting path strategy in machining; optimization of cutting parameters (cutting speed, feed rate, and depth of cut); CNC machining for ball valve components; design of a ball valve plastic lever; design of a ball valve plastic lever mold; and molding of a ball valve plastic lever; assembly of ball valve components; hydraulic testing at a pressure of 10 Bar; and quality-dimensional and packaging inspection. The production results are in the form of a ball valve with a valve housing made of stainless steel, SS304 with a valve ball diameter of 0.5” with a total production cost of IDR 75,000/unit, and a process duration of 30 minutes/unit which means that the ball valve can be used in various water installations in industrial areas and in household environments.